Influência da concentração de alcalinidade e relação C/N no processo de nitrificação e desnitrificação simultânea de efluente de microcervejaria em um reator de leito estruturado - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
Dumping of effluents rich in nitrogen can cause the eutrophication in water bodies, with consequent depletion of the oxygen concentration and death of the aerobic beings. The technologies most used for nitrogen removal use more than one unit process. Studies show the possibility of removing COD (Chemical Oxygen Demand) and nitrogen in a single compartment, which would generate savings in the implementation and operation of ETPs (Effluent Treatment Plants). The objective of this work was to evaluate the influence of the alkalinity concentration and C/N ratio on the simultaneous nitrification and denitrification of microbrewery effluent in a structured bed reactor and continuous flow with intermittent aeration and effluent recirculation. The reactor had a useful volume of 8.4 L. The structured bed was composed of 45 Biobobs®, arranged vertically inside the reactor. The recirculation ratio was equal to 2 times the inlet flow rate. To evaluate the performance of the reactor, 2 alkalinity conditions, with and without correction, and 3 C/N ratio conditions expressed in terms of COD/TKN equal to 2, 6 and 10 were tested, resulting in an experiment with 6 trials. The COD/TKN ratio was varied by keeping the COD concentration fixed at 600 mg COD.L-1 , and changing the concentration of nitrogen by the addition of ammonium chloride (NH4Cl). The alkalinity correction of the influent was performed according to the TKN value for each studied condition. For each mg of TKN present in the influent, 7.14 mg of calcium carbonate (CaCO3) was required. Under the conditions studied, the average COD reduction was 88% and the best TN (total nitrogen) reduction was 32.6%. The best COD reduction efficiency result of 94% was in condition 6 with the COD/TKN ratio of 10, without correction of the alkalinity of the influent. The highest TN removal efficiency (32.6%), was obtained in condition 1 with the COD/TKN ratio of 10, with correction of the alkalinity of the influent. From the results obtained in this work, it was possible to observe that the lower N-ammoniacal concentration in the influent, higher was the nitrification efficiency obtained. The denitrification efficiency was satisfactory and the presence of nitrate was not detected in any of the conditions tested.
Keywords: Efluente de microcervejaria; nitrificação e desnitrificação simultânea (NDS); reator de leito estruturado; aeração intermitente; Microbrewery wastewater; simultaneous nitrification and denitrification (SND); structured bed biofilm reactor; intermittent aeration; CNPQ::ENGENHARIAS::ENGENHARIA SANITARIA